Strong inflammatory signatures in the neutrophils of PAMI syndrome - Zheng, Wenjie; Fan, Xiaorui; Yang, Zhaohui; Shangguan, Yaoyao; Jin, Taijie; Liu, Yan; Huang, Jiqian; Ye, Xiaohua; Zhou, Qing; Li, Xiaozhong (Frontiers in Immunology, 2022)
PSTPIP1 (proline-serine-threonine phosphatase-interactive protein 1)–associated myeloid-related proteinemia inflammatory (PAMI) syndrome is a rare autoinflammatory disease caused by heterozygous gain-of-function mutation in PSTPIP1. As one of the PSTPIP1-associated inflammatory diseases (PAIDs), neutropenia is a distinct manifestation to separate PAMI syndrome from other PAIDs. This study aimed to investigate the potential role of neutrophils and inflammatory signatures in the pathogenesis of PAMI. PAMI neutrophils displayed markedly increased production of interleukin-1β (IL-1β) and IL-18 by enzyme linked immunosorbent assay (ELISA) assay and intracellular cytokine staining. ASC speck formation and lactic dehydrogenase (LDH) release are also increased in patient neutrophils suggesting elevated pyrin inflammasome activation followed by upregulated cell death in PAMI neutrophils. RNA sequencing result showed strong inflammatory signals in both nuclear-factor kappa B (NF-κB) pathway and interferon (IFN) pathway in patient neutrophils. This study highlighted that elevated proinflammatory cytokines IL-1β and IL-18, increased pyrin inflammasome activation, and upregulation of NF-κB and IFN signaling pathways in neutrophils play important roles in pathogenicity of PAMI syndrome.